2021
DOI: 10.3390/ma14102487
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Wear Behavior Analysis of Coated Spindle Hook Teeth under Real Harvesting Work Conditions

Abstract: This study aimed to investigate the wear failure changes of spindle hook teeth and the reasons for such failure during field work. Spindle samples were obtained from a fixed position of the spindle bar under different field picking area conditions and combined with the spatial distribution characteristics of cotton bolls in Xinjiang. After cutting a spindle sample, a scanning electron microscope and an energy spectrum analyzer were used to characterize the micromorphology and element composition of the hook to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The spindle is a key core component of the cotton picker, and its performance directly determines the picking efficiency and effect of the cotton picker field operation (Chen et al, 2020b;Bi, 2007;Li et al, 2022b). At the same time, the spindle is also the most consumed among wear parts on the cotton picker, and spindle hook teeth are very prone to wear failure problems (Wu et al, 2013;Zhang et al, 2017;Li et al, 2018;Gu et al, 2021;Li et al, 2022a). The wear failure of spindle will lead to a decrease in cotton harvesting rate of the cotton picker during field operation and serious wastage.…”
Section: Introductionmentioning
confidence: 99%
“…The spindle is a key core component of the cotton picker, and its performance directly determines the picking efficiency and effect of the cotton picker field operation (Chen et al, 2020b;Bi, 2007;Li et al, 2022b). At the same time, the spindle is also the most consumed among wear parts on the cotton picker, and spindle hook teeth are very prone to wear failure problems (Wu et al, 2013;Zhang et al, 2017;Li et al, 2018;Gu et al, 2021;Li et al, 2022a). The wear failure of spindle will lead to a decrease in cotton harvesting rate of the cotton picker during field operation and serious wastage.…”
Section: Introductionmentioning
confidence: 99%
“…6–9 In the process of the cotton harvesting operation, the friction between the high-speed rotating cotton-picking head and the cotton stalk easily produces sparks, and these sparks are unavoidably wrapped in the cotton. 10,11 Consequently, early fire, namely smoldering, occurs inside the cotton, which is flameless and difficult to detect. 12 Once smoldering changes to flaming combustion and fire, great threats are posed to the safety and lives of people and property.…”
Section: Introductionmentioning
confidence: 99%
“…As is known [11,12], the process of drawing-in and compression of a cotton plant and its elements through the working area formed by two parallel spindle drums depends on the linear velocity of rotation of the spindles, the peripheral velocity of the spindle drum and the movement of the branches of the cotton plant. Experimental studies have shown [13][14][15] that an increase in the productivity of cotton harvesters (serial and improved ones) with epi-and hypo-cyclic spindle drives with the same working width and the same agricultural background is ensured by increasing the length of furrows, the speed of the cotton harvester, and the completeness of the cotton harvest.…”
Section: Introductionmentioning
confidence: 99%